2022
DOI: 10.1097/md.0000000000029032
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of massage adjuvant therapy in the treatment of diabetic peripheral neuropathy

Abstract: BackgroundThe incidence of diabetic peripheral neuropathy (DPN) is increasing year by year. If patients cannot receive timely and effective treatment, DPN may lead to diabetic foot ulcers or even amputation. This risk factor has been widely concerned around the world. Massage, as a non-invasive physical therapy method, is gradually being applied in the adjuvant treatment of DPN. However, there is no systematic review of the adjuvant treatment of DPN by massage. Our study will explore the effectiveness and safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…However, this treatment plan can only alleviate clinical symptoms and signs, and has lower significance in improving the condition. Zinc sulfate, as a coenzyme, exists in the mitochondrial enzyme and can be biotransformation into reduced dihydrogen sulfate (18). The application of sufficient doses of zinc sulfate can effectively eliminate free radicals and chelated metal ions in the body, enabling them to generate other antioxidants and have significant antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, this treatment plan can only alleviate clinical symptoms and signs, and has lower significance in improving the condition. Zinc sulfate, as a coenzyme, exists in the mitochondrial enzyme and can be biotransformation into reduced dihydrogen sulfate (18). The application of sufficient doses of zinc sulfate can effectively eliminate free radicals and chelated metal ions in the body, enabling them to generate other antioxidants and have significant antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 9 studies did not use acupoint massage alone, and 7 studies lacked the outcome measure, total effectiveness, or SCV, or TCSS. At the end of the selection process, 20 studies met the inclusion criteria (Figure 1) [26][27][28][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] After assessing the Cochrane tool ROB-2, the condition of studies quality came out. (Figure 2) displays the overall quality of studies, which showed approximately 22.2% low risk, 66.7% some concerns and 11.1% high risk of Overall bias.…”
Section: Literature Searchmentioning
confidence: 99%
“…As shown in Figure 3, we saw that some studies had several items of high risk. Comparatively, Tian [42] and Zhu [39] got a bad performance on bias of deviations from intended interventions, which rarely displayed information about intervention [39][40][41][42] and Zhang [43] got a good grade which owned four low risk of bias, while Liang [48] and Huang [26] only had two low-risk items [26,28,43].…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods have also been reported such as the consumption of antioxidants, supplementation of nerve growth factors, and the administration of immunosuppressants [ 10 , 11 ]. However, there is currently no specific and satisfactory therapeutic method in clinical practice [ 12 ]. Professor Dellon found that the sensitivity of peripheral nerves to compression increased during diabetes, and demonstrated that the symptoms of DPN were caused by nerve compression, and after taking the lead in the treatment of DPN with peripheral nerve decompression microsurgery, the surgery was effective, and the course of DPN changed [ 13 ].…”
Section: Introductionmentioning
confidence: 99%